2005
DOI: 10.1111/j.1600-051x.2005.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional intelligence and initial response to a standardized periodontal treatment

Abstract: This pilot study demonstrated an association between EI domains and short-term changes in plaque and bleeding, and suggest that initial responses to standardized periodontal treatment may be partly related to EI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…This pilot study demonstrated an association between EI domains and short-term changes in plaque and bleeding, and suggest that initial responses to standardized periodontal treatment may be partly related to EI. (25) Thus , in our present study , the socio-economic and behavioural factors such as tobacco smoking were found to be related to treatment outcome measures in terms of plaque index, bleeding index , probing depth and clinical attachment loss. The size of the sample was small and did not allow for multivariate modelling.…”
Section: Discussionsupporting
confidence: 47%
“…This pilot study demonstrated an association between EI domains and short-term changes in plaque and bleeding, and suggest that initial responses to standardized periodontal treatment may be partly related to EI. (25) Thus , in our present study , the socio-economic and behavioural factors such as tobacco smoking were found to be related to treatment outcome measures in terms of plaque index, bleeding index , probing depth and clinical attachment loss. The size of the sample was small and did not allow for multivariate modelling.…”
Section: Discussionsupporting
confidence: 47%
“…The first is a small pilot study by Gamboa, Hughes, and Marcenes (2005), who followed the progress of 29 dental patients for three weeks after they completed a standardised two-visit treatment protocol for chronic periodontitis. On each visit, the patients received supra-gingival scaling and polishing and were instructed on proper oral hygiene practices (e.g., tooth brushing, flossing, tongue brushing) to be followed at home.…”
Section: Medical Regimenmentioning
confidence: 99%
“…An association between emotional intelligence domains (emotional awareness, competencies, values and beliefs) and shortterm changes in plaque and bleeding was revealed, suggesting that initial responses to standardized periodontal treatment may be partly related to emotional intelligence (66). In a sample of first-year students, emotional intelligence levels were related to self-reported oral health status, dental visit frequency, and reasons for visiting a dentist (67).…”
Section: Discussionmentioning
confidence: 99%